RANCANGAN APLIKASI DATA FLIGHT DAILY INWARD/OUTWARD TRAFFIC RECORD PADA UNIT ATS-RO DI PERUM LPPNPI CABANG BALIKPAPAN - Novansyah Adi Pangestu; Meita Maharani Sukma; Siti Nurfadhilah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The daily inward/outward traffic record form has an important role in unit ATS-RO (Air Traffic Service Reporthing Office). The daily inward/ouward traffic record form serves as a reference for airlines that have six months (summer/winter) at Sultan Aji Muhammad Sulaiman Airport. The problem that is reviewed in writing this final project is about the inefficient form of daily inward/outward traffic record, which are still being carried out manually on paper, so it has an impact on difficulties in monitoring aircraft that have departure/arrival at Perum LPPNPI Cabang Balikpapan. The research method in used in this research the final project use is descriptive research design,namely data collertion techniques using, observations, interviews, case studieand literature studies. The daily inward/outward traffic record form is used in services at the unit ATS-RO (Air Traffic Service Reporthing Office) at Perum LPPNPI Cabang Balikpapan. With the daily inward/outward traffic record form not yet maximized, so that suggeestions can be taken, an effective and efficient daily inward/outward traffic record data application must be made to minimize data errors when carrying out on duty in the (Air Traffic Service Reporthing Office).